External activity of colonies of Melipona quinquefasciata managed in different types of beehive - Mascena, Valdenio; Silva, Celso; Almeida, Cicero; Alves, Társio Thiago; Freitas, Breno (Revista Ciência Agronômica, 2018)
This study evaluated the influence of the environment and of two models of beehive (wooden box and ceramic pot) on the flight activity of the ground-nesting bee, Melipona quinquefasciata. The experiment took place in the Chapada do Araripe, in the State of Ceará, Brazil, between July 2014 and June 2015. The study followed colonies in three ceramic pots and four wooden boxes. Observations of the flight activity of the bees and of the climate were made on five days every month, each colony being monitored for 5 min, at intervals of one hour, from 0500 to 1700. The internal temperature and relative humidity of the hives were also recorded every hour throughout the year. The temperature correlated positively with the bees’ entering and leaving the hives, while air humidity correlated negatively. Light intensity positively influenced the two flows. Bee entry was higher during the dry period of the year (dry = 2.82 ± 0.22; wet = 1.19 ± 0.22). The mean internal temperature of the ceramic pots was higher (p